FINANCIAL STATEMENT ANALYSIS AS A TOOL FOR FINANCIAL PERFORMANCE ASSESSMENT (STUDY OF MULTI-BUSINESS COOPERATIVES IN DUKUH MENANGGAL SUB-DISTRICT, SURABAYA) - Samsiyah, Siti; Firdausia, Yuli Kurnia (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
This research aims to determine the financial performance of the Multi-Enterprise Cooperative in the Dukuh Menanggal district of Surabaya in 2018 - 2022 using the Trend Common Size Financial Statement Method and financial ratio analysis. The object used in this research is the analysis of financial reports for five years, namely 2018 - 2022. Multi-Enterprise Cooperative, Dukuh Menanggal sub-district, Surabaya a. The population in this study is the entire financial report of the Multi-Purpose Cooperative, Dukuh Menanggal sub-district, Surabaya. The sample is a portion of the financial report from the Multi-Purpose Cooperative, Dukuh Menanggal sub-district, Surabaya financial report in 2018 - 2022. The data analysis method in the financial report is used to measure, know, describe, determine and compare the proportions of the items in the report balance sheet, profit and loss and cash flow. The results of the Common-size analysis show that short-term financial conditions seen from the percentage of current liabilities to total liabilities tend to increase. As well as showing the condition of business results seen from the Net profit, it shows that the percentage of net profit to revenue tends to increase. Overall, the financial performance of the Multipurpose Cooperative, Dukuh Menanggal subdistrict, Surabaya is in good condition